2013
DOI: 10.1084/jem.20130012
|View full text |Cite
|
Sign up to set email alerts
|

IL28B expression depends on a novel TT/-G polymorphism which improves HCV clearance prediction

Abstract: A new polymorphism near the IL28B locus negatively affects induction of IL28B and exhibits strong predictive value for HCV treatment response and spontaneous resolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
199
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 188 publications
(221 citation statements)
references
References 27 publications
17
199
0
5
Order By: Relevance
“…A recent key discovery identified the IFNL4 gene and showed that a polymorphism (rs368234815), which causes the disruption of the IFNL4 reading frame, correlates with a substantially better treatment response 15,16 as well as better spontaneous clearance rate 13 . Thus, patients having a nonfunctional IFNL4 gene are more likely to clear the HCV infection.…”
mentioning
confidence: 99%
“…A recent key discovery identified the IFNL4 gene and showed that a polymorphism (rs368234815), which causes the disruption of the IFNL4 reading frame, correlates with a substantially better treatment response 15,16 as well as better spontaneous clearance rate 13 . Thus, patients having a nonfunctional IFNL4 gene are more likely to clear the HCV infection.…”
mentioning
confidence: 99%
“…However, none of these studies have exclusively examined this SNP in genotype 3 HCV patients.Besides these three studies, others have failed to show any significant association betweenIL28B polymorphisms and SVR in genotypes 2 and 3 HCV-infected patients 32 although all studies have shown an association with RVR. A recent report also shows significant association between a novelIL28B SNP (ss469415590; encoding IFN-L4) with SVR 33 in genotype 2/3 HCV infections.Therefore, the association of IL28B SNPs and SVR in genotype 2/3 HCV infections remains controversial. The present study shows that the rs8099917 SNP is associated with both RVR and SVR in genotype 3 patients, though the association is weak and shows no association with relapse.The latter is a relatively novel finding, and raises the need for larger studies to validate the role of IL28B polymorphism singenotype 3 treatment outcome.…”
Section: Introductionmentioning
confidence: 91%
“…This has been fine mapped to the TT/‐G polymorphism at rs67272382 in a CpG island, which is in strong linkage disequilibrium with IFN‐λ3 and is most likely to be the causal variant, with the possibility of defining a new type 3 IFN, IFN‐λ4 10, 11. Whilst this polymorphism has shown remarkable consistency in its ability to predict spontaneous and treatment‐induced viral clearance across populations, its protection does not extend to ‘exposed uninfected’ individuals, suggesting that multiple pathways to clearance may coexist within a population 12, 13.…”
Section: Introductionmentioning
confidence: 99%